Peningkatan Kemampuan Pengelolaan Keuangan Keluarga melalui Pelatihan Keuangan Keluarga pada Majelis Taklim Kaum Ibu Al -Barokah Tambun Selatan - Yahya, Adibah; Kosim, Muhammad; Achmad, Listrian Indriyani; Amrulloh, Azmi (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2023)
Community service activities are one of the components of the Tridharma (three duty of lecturers) of Higher Education   Because every lecturer has obligations, to do community service. The service that we carried out was training in family financial management, focusing activities on improving the ability to manage family finances. The targets for this community service were mothers who are members of Majelis Taklim Al-Barokah South of Tambun. The method used in this service is training and also assistance on family financial management. The results of this service show that the women of the Majelis Taklim were very enthusiastic about participating in financial management training. Furthermore, with the implementation of this service activity, the community, especially housewives, have more ability to manage household finances, and are also able to provide more support so that housewives can avoid moneylenders. Further service activities   expected to be able to provide continuous training that triggers the spirit of housewives to generate their own income in order to improve the welfare of their family life.